Isolation in Commodity Multicore Processors. - Aggarwal, Nidhi; Ranganthan, Parthasarathy; Jouppi, Norman P.; Smith, James E. (Computer (00189162), 2007)
The article discusses features designed to protect multiprocessors from faults and security breaches. Chip multiprocessors (CMPs) feature multiple cores allowing high levels of integration. The scaling of technology can lead to hardware errors such as silicon defects or sort errors from electrical noise and radiation. Static isolation of CMPs can affect system performance. Configurable isolation is a computer architecture which controls resource sharing to provide different isolation levels. Computer simulations indicate performance degradation is more gradual in systems featuring configurable isolation. INSET: Other Benefits from Isolation.